Anxious individuals have difficulty learning the causal statistics of aversive environments - Browning, Michael (Nat Neurosci, 2015)
Statistical regularities in the causal structure of the environment enable us to predict the probable outcomes of our actions. Environments differ in the extent to which action-outcome contingencies are stable or volatile. Difficulty in being able to use this information to optimally update outcome predictions might contribute to the decision-making difficulties seen in anxiety. We tested this using an aversive learning task manipulating environmental volatility. Low trait anxious human participants matched updating of their outcome predictions to the volatility of the current environment, as predicted by a Bayesian model. High trait anxious individuals showed less ability to adjust updating of outcome expectancies between stable and volatile environments. This was linked to reduced sensitivity of the pupil dilatory response to volatility, potentially indicative of altered norepinephrinergic responsivity to changes in this aspect of environmental information.